2021
DOI: 10.3389/fpsyt.2021.704174
|View full text |Cite
|
Sign up to set email alerts
|

Spider Phobia: Neural Networks Informing Diagnosis and (Virtual/Augmented Reality-Based) Cognitive Behavioral Psychotherapy—A Narrative Review

Abstract: Recent fMRI studies on specific animal phobias, particularly spider phobia (arachnophobia), have identified a large variety of specific brain regions involved in normal and disturbed fear processing. Both functional and structural brain abnormalities have been identified among phobic patients. Current research suggests that both conscious and subconscious fear processing play a crucial role in phobic disorders. Cognitive behavioral therapy has been identified as an effective treatment for specific phobias and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 95 publications
0
7
0
3
Order By: Relevance
“…Table 1 presents and indicates examples of neuroscientific areas of using virtual environments and tools, including pain management [31,[56][57][58], improvement of brain injury patients [5,26,[59][60][61], post-stroke [10,20,25,33,[65][66][67], prevention, and diagnosis and therapy of many serious illnesses. Examples include diseases such as neurodevelopmental disorders (e.g., attentiondeficit hyperactivity disorder, ADHD [22,80,81]); schizophrenia spectrum disorders (e.g., schizophrenia [82,83]); autism spectrum disorders (e.g., autism [84,85]); mood (e.g., depressive disorders [86,87]), anxiety (e.g., panic and phobias [74][75][76]), trauma-and stressorrelated (e.g., post-traumatic stress disorder, PTSD [73]), neurocognitive (e.g., Parkinson's or Alzheimer's and memory cognitive impairment diseases [23,24,47,[69][70][71][72][77][78][79]) and neuromuscular disorders (e.g., multiple sclerosis [32,[62][63]…”
Section: Hinze Et Al 2021 [76]mentioning
confidence: 99%
“…Table 1 presents and indicates examples of neuroscientific areas of using virtual environments and tools, including pain management [31,[56][57][58], improvement of brain injury patients [5,26,[59][60][61], post-stroke [10,20,25,33,[65][66][67], prevention, and diagnosis and therapy of many serious illnesses. Examples include diseases such as neurodevelopmental disorders (e.g., attentiondeficit hyperactivity disorder, ADHD [22,80,81]); schizophrenia spectrum disorders (e.g., schizophrenia [82,83]); autism spectrum disorders (e.g., autism [84,85]); mood (e.g., depressive disorders [86,87]), anxiety (e.g., panic and phobias [74][75][76]), trauma-and stressorrelated (e.g., post-traumatic stress disorder, PTSD [73]), neurocognitive (e.g., Parkinson's or Alzheimer's and memory cognitive impairment diseases [23,24,47,[69][70][71][72][77][78][79]) and neuromuscular disorders (e.g., multiple sclerosis [32,[62][63]…”
Section: Hinze Et Al 2021 [76]mentioning
confidence: 99%
“…Particularly functional magnetic resonance imaging (fMRI) has revealed brain correlates of emotions and psychological dimensions relevant to spider phobia (for a review, see Hinze et al, 2021). Neuroimaging studies have identified a so-called “fear network” in the processing of spider-related stimuli, which consists of the amygdala, the insula and the anterior cingulate cortex (Hinze et al, 2021; Holzschneider & Mulert, 2011). Other studies have suggested that disgust, which has been linked to the prevention of contamination (e.g., Davey, 1994; Gerdes et al, 2009; Olatunji & McKay, 2006), is associated with overlapping but distinct neural activation compared to fear (Stark et al, 2007).…”
Section: Background and Summarymentioning
confidence: 99%
“…With the help of neuroimaging, researchers can gain insights into the neural underpinnings of such specific phobias. Particularly functional magnetic resonance imaging (fMRI) has revealed brain correlates of emotions and psychological dimensions relevant to spider phobia (for a review, see Hinze et al, 2021). Neuroimaging studies have identified a so-called “fear network” in the processing of spider-related stimuli, which consists of the amygdala, the insula and the anterior cingulate cortex (Hinze et al, 2021; Holzschneider & Mulert, 2011).…”
Section: Background and Summarymentioning
confidence: 99%
“…Conversely, AR may be viewed as easier to use because it refers to I-PAD, tablets, and smartphones, which are more suitable to the real world (Bekkers et al, 2020 ; Held et al, 2020 ; Levin and Demers, 2021 ). Although widely used in patients with disorders of consciousness (Hinze et al, 2021 ; Kwok et al, 2021 ), to the best of our knowledge it has never been used in patients with acquired brain injuries, history of coma and post-coma outcomes, except for the contribution of Maggio et al ( 2020 ). Although it may be considered as ethically controversial and questionable, such hypothesis undoubtedly merits to be empirically tested, eventually integrated with an assistive technology device, for both assessment and recovery goals.…”
Section: Virtual Realitymentioning
confidence: 99%